Asuhan Keperawatan Dengan Berat Badan Lahir Rendah (BBLR) : Studi Kasus: Asuhan Keperawatan Dengan Berat Badan Lahir Rendah (BBLR) : Studi Kasus - Ulfianasari, Evri; Perdani, Zulia Putri; Zulia Putri (Jurnal Kesehatan Masa Depan, 2023)
Abstract :Premature LBW babies are babies born weighing less than or equal to 2500 grams regardless of gestational age with a gestational age of less than 37 weeks. World Health Organization data shows that premature births in the world reach 4.5 million babies from all births, while the incidence of LBW is 15.5%, which means around 20.6 million babies, 96.5% of them in developing countries .The purpose of this study was to determine nursing care for neonates withLow Birth Weight Babies. This research is a qualitative research with a case study design using the nursing process approach. The population in this study were neonates who experiencedLow Birth Weight Babies. The sample is By.P. The sampling technique used is purposive sampling. The research was conducted at the Tangerang Regency Hospital in January 2023. Data collection was carried out by interviews, observations, and documentation studies. The research instrument was the researcher himself with the aid of a sphygmomanometer, stethoscope, thermometer, penlight, and assessment guidelines. Based on the studies conducted, it was found that TTV data: S = 35.20 C, N = 140 x/minute, RR = 68 x/minute;Dyspnea, use of accessory muscles to breathe, nostril breathing,skin feels cold, looks pale, dry lip mucosa, nutrition: 350 ml of breast milk every 3 hours, Hemoglobin: 15.1.2 gr/dl, leukocytes 16.51 µL; Quantitative CRP 15.54mg/L. There are 3 nursing problems, namely ineffective breathing pattern, ineffective thermoregulation, risk of infection. After nursing care was carried out for three days, the development of the problem improved. In conclusion, the main nursing problem in By.P with fast breathing frequency was ineffective breathing pattern.